VALIDITAS HADIS-HADIS PADA BUKU “MATERI KHOTBAH JUMAT SETAHUN” KARYA AHMAD YANI - Muhammad, Zaki (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2021)
Many books about religious sermon for Jumat prayer contain many hadiths and are popular among khatib (preachers). Ideally, the hadiths derive from standard books of hadith written by recognised imams. However, some authors incorporating hadiths into the religious sermon books neglect therules of hadith quotation. They include hadith without attaching hadith resources (transmitters). As a result, the hadiths doubtful in terms of authenticity and validity. As the religious sermon books become vouge among khatib (preachers), many khatibs uncritically quote the hadiths and deliver them to jamaah during Jumat prayer. This paper aims to examine the method of the hadiths incorporation and their authenticity in the religious sermon book of Materi Khotbah Jumat Setahun written by Ahmad Yani. This book is selected as it becomes vogue among khatib (preachers). This study constitutes library research employing hadith science approach as data analysis. The findings of this study are presented descriptively and qualitatively. This paper finds that firtsly, the writer of the book partly comply with the methods of hadith quotation as required by ilmu hadith (the prophet tradition science). Secondly, the authenticity of the hadith the author quotes varies from shahîh, hasan, dhaîf, and laysa bihadith. However, the hadith that shahîh (authentic) outnumbers the others, i.e. 34 out 49 hadiths examined are authentic (69%). This paper recommends that the book of Materi Khotbah Jumat Setahun is appropriate for khatib guidance in delivering religious sermon for Jumat prayer.